Collaborative Rural Community Energy Planning: The Health and Economic Benefits of Walking the Talk (breakout presentation). (December 2017) - Dehnel, Patricia; Wall, Kerri; Adams, Mike; Pollock, Sue
Abstract : Background: British Columbia legislation requires Local Governments to make efforts to reduce community greenhouse gas emissions. This powerful provincial statement provides the impetus and Carbon Tax funding to create collaborations, develop opportunities to increase energy efficiency, provide community financial savings and develop infrastructure to encourage and promote healthy lifestyles. In the primarily rural southeastern Kootenay Region, all small and mid-size communities are taking action to improve their energy resilience, and have found the economic and health implications of plan implementation to be astounding. Description of Program: Community Energy Plans in rural communities provide direction to develop active transportation plans, improve walking infrastructure and promote a healthy lifestyle. All while reducing greenhouse gas emissions. With appealing walking infrastructure, in theory, most people will walk short distances. The plans support this theory and all the associated health benefits. Policy: Community Energy Plans adopted to address reductions in community Greenhouse Gas Emissions have become the framework to apply for "Plan H" funding for sidewalk infrastructure, Active Transportation plans, walking school bus programs, etc., within the BC Interior Health region. Outcomes: Community Energy Plans engage the community, support healthy transportation choices and develop a collaborative inclusive community resilience. What began as a plan to reduce greenhouse gas emissions, through community involvement, innovation and resolution, develops into an age-friendly, walkable rural community. Lessons Learned: Reframe the message of Greenhouse Gas Reductions and Carbon Tax to "build community". The result is the co-benefits of active transportation and a healthy population. Implications: Communities are working to meet their reduction targets and our population is more active. An active person reduces their chance of chronic disease (i.e., diabetes and cardiovascular disease). Community planning and design can influence the health of the population. One in three British Columbians is living with chronic disease. 50% of adults and 91% of children/youth do not have recommended levels of physical activity. Recommendations: Community collaboration is key. Partnerships with the province and utilities to support development of Community Energy Plans unique to each place. The plans are the impetus for developing infrastructure to "walk the talk". An active and engaged community results.